1997
DOI: 10.1007/bf02784439
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of zinc in intracellular oxidant/antioxidant balance

Abstract: The effect of zinc (Zn) on cellular oxidative metabolism is complex and could be explained by multiple complementary interactions. In this study, we evaluated the impact of Zn on the pro-oxidant/antioxidant balance of HaCaT keratinocytes. Cells were submitted to a diffusible metal chelator able to induce intracellular Zn deprivation, TPEN, in combination or not with Zn chloride (ZnCl2), in the culture medium. The intracellular amount of Zn, copper (Cu), and iron (Fe) was determined, as well as CuZnSOD and MnSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 38 publications
3
34
0
1
Order By: Relevance
“…We studied Zn-related detoxification factors, such as metallothioneins (17), GSH (18), and the GSH-coupled excretory pump GS-X (4), and we observed that intracellular GSH was high in PC/RES cells (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…We studied Zn-related detoxification factors, such as metallothioneins (17), GSH (18), and the GSH-coupled excretory pump GS-X (4), and we observed that intracellular GSH was high in PC/RES cells (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Zn has catalytic and structural roles in more than 300 metalloenzymes, as well as regulatory roles in diverse cellular processes such as signaling transduction and gene expression (McCall et al, 2000). Many studies have demonstrated that Zn per se functions as antioxidant and also plays an important role in regulation of cellular glutathione (GSH) (Parat et al, 1997;Powell, 2000;Zhou et al, 2005). Although GSH is the most important molecule involved in cellular antioxidant defense, radical scavenging activity of GSH is 300-times lower than that of MT (Thornalley and Vasak, 1985).…”
Section: Effect Of Zn and CD Against Acute Ccl 4 Toxicitymentioning
confidence: 99%
“…Radikal bebas dan senyawa oksigen reaktif yang diproduksi dalam jumlah yang normal, penting untuk fungsi biologis, namun ia tidak menyerang sasaran spesifik, sehingga ia juga akan menyerang asam lemak tidak jenuh ganda dari membran sel, organel sel atau deoxyribonucleid acid (DNA), hal ini dapat menyebabkan kerusakan struktur dan fungsi sel (Winarsi, 2007). Lebih lanjut Parat et al (1997) menyatakan bahwa stres oksidatif dapat mengakibatkan terjadinya kematian sel (nekrosis). Menurunnya jumlah eritrosit pada perlakuan pada P2 dan P3 diduga karena adanya nekrosis atau kerusakan jaringan pada organ pembentukan sel-sel darah pada ikan nila.…”
Section: Tabel 1 Rata-rata (±Sd) Jumlah Eritrosit Ikan Nila Pada Masunclassified